PEMBERDAYAAN KAMPUNG BUMI JAYA MELALUI HARI ULANGTAHUN BUMI JAYA SEBAGAI SARANA MENJALIN KEKELUARGAAN, PERTUNJUKAN SENI, DAN KESEHATAN - Sumargono; Hutabarat, Atha Gunadi; Wiranata, Seftian; Cahyani, Regita Gustiana; Nafisah, Afaf; Mayola, Rosya; Amanah, Miftakhul; Sagefi, Maylania Herlis; Prianjani, Ajeng; A.L.D, M. Ferdiansyah; Cahyarani, Abethia (Badan Pelaksana Kuliah Kerja Nyata Universitas Lampung, 2025)
This journal discusses the empowerment of Bumi Jaya village through the anniversary of Bumi Jaya as a means of establishing kinship, performing arts, and health. Bumi Jaya is one of the villages that is the target of KKN at the University of Lampung. Kampung Bumi Jaya is in the Negara Batin sub-district, Way Kanan district, Lampung province. Kampung Bumi Jaya was established on January 1, 1984 and was inaugurated on January 24, 1984. In 2023 there will be 6 hamlets/families divided into 21 RTs with a total of 1,178 households. The majority of the livelihoods of the people of Bumi Jaya are farmers and farm labourers. Facilities and infrastructure in Bumi Jaya village are complete and adequate. However, even though the facilities and infrastructure were adequate, there were drawbacks, namely never celebrating the anniversary of the village of Bumi Jaya with great fanfare with various activities. So people don't celebrate. The purpose of the Community Service program for students at the University of Lampung is to celebrate Bumi Jaya's anniversary in a festive manner, namely so that residents know the history of Bumi Jaya village, establish a sense of kinship, preserve the arts, and provide physical and spiritual health. Journal research and writing using field research. While the method used is journal writing with a qualitative approach, descriptive-explanative model which intends to provide a detailed description of the Bumi Jaya Anniversary commemoration program during the Field Work Lecture.